Criminal Policy Corruption Natural Resources In The Fisheries Sector - Asis, Abd; Lewerissa, Yanti Amelia (SASI, 2023)
Introduction: The criminal policy of natural resource corruption in the fisheries sector can be carried out using two approaches, namely the penal approach and the non-penal approach.Purposes of the Research: .Methods of the Research: This research method is normative juridical while still involving the role of other social sciences in legal social studies. The approach used in this research is a statutory approach and a conceptual approach. Data collection was carried out by literature study and then analyzed qualitatively.Results of the Research: IUU Fishing practices such as transshipment, fraudulent acts of marking down ship sizes, using unreported foreign crew members or using falsified documents, bribing bribes in permit processing and various actions that lead to corrupt practices in the fisheries sector cause the country to suffer huge losses and have a bad impact on the country. people's welfare and exploitation of natural resources that can damage the ecosystem. For this reason, there is a need for criminal policy or efforts to overcome corruption by using two approaches, namely a repressive penal approach and a preventive non-penal approach.